Real Ileal Digestibility of Sunflower Protein and Amino Acids in Humans. (29th May 2020) - Tessier, Romain; Calvez, Juliane; Khodorova, Nadezda; Quinsac, Alain; Kapel, Romain; Galet, Olivier; Tomé, Daniel; Airinei, Gheorghe; Benamouzig, Robert; Gaudichon, Claire
Abstract: Objectives: Sunflower protein has a relatively well-balanced amino acid profile but it is little used in human food. Nutritional quality of sunflower protein isolate has never been directly measured in humans. This study aims to determine the ileal digestibility of protein and amino acid of a sunflower isolate incorporated in biscuits, in healthy humans. Methods: Healthy volunteers ( n  = 7) were intubated with a naso-ileal tube. They ingested every 30 min for 4 h, sunflower biscuits for a total of 156 g of biscuits and 25 g of 15 N intrinsically labeled sunflower protein isolate. A non-absorbable marker was perfused into the ileum. Ileal samples were continuously collected during 8 h after the first meal. Blood was sampled every 30 min for 4 h and every hour after and total urine was collected every 2 h. To measure nitrogen ileal digestibility, the percentage of nitrogen and 15 N enrichment in ileal contents were assessed by an elemental analyzer coupled with and isotope ratio mass spectrometer (EA-IRMS). Indispensable amino acid (IAA) ileal digestibility was determined by measuring amino acid 15 N enrichment by GC-C-IRMS and their quantification by UHPLC. Metabolic losses of dietary nitrogen were assessed by measuring 15 N in urine and plasma. The digestible indispensable amino acid score (DIAAS) and the net post-prandial utilization (NPPU) were calculated. Results: Exogenous nitrogen appeared in the ileum 1 h after the first meal, its flow was stable between 4 h and 7 h. Cumulated dietary nitrogen in the ileum was 14.0 ± 4.0% over 8 h. Sunflower nitrogen real ileal digestibility was 86.0 ± 4.0% of ingested nitrogen. Mean IAA ileal digestibility was 87.0 ± 6.1% with values ranging from 84.4% for lysine and threonine to 89.3 ± 7.8% for methionine. DIAAS was 0.93 for lysine. After 8 h, 4.0 ± 1.0% of dietary nitrogen was incorporated in plasma protein. Cumulated exogenous nitrogen in urinary urea was 4.0 ± 1.4% and exogenous nitrogen in body urea after 8 h was 9.8 ± 2.5%. The NPPU was 72.2 ± 3.7% at 8 h. Conclusions: Sunflower isolate ileal digestibility is relatively low compared to other protein isolate assessed in similar conditions (ileal tube and 15 N labeling of protein). Despite a moderate deficiency in lysine, sunflower protein isolate has a good post-prandial metabolic utilization. Funding Sources: French Research National Agency (ANR), financial support of SOFIPROTEOL under the FASO Project PRODIA.